Mwcnt-Organoimido Polyoxomolybdate Hybrid Material: Analytical Applications for Amperometric Sensing of Hydrogen Peroxide - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (John Wiley and Sons Inc, 2021)
We report a hybrid material obtained by dispersing the polyoxometalate n-[Bu4-N]2[Mo6O18NC13H9] functionalized with 2-aminofluorene (POMAF) and multi-walled carbon nanotubes (MWCNTs) in 1,3-dioxolane (MWCNT- POMAF). We demonstrate the peroxidase-like activity of the hybrid material and its application for the amperometric quantification of hydrogen peroxide at −0.450 V previous drop-coating at glassy carbon electrodes, with a linear range between 1.0 μM and 6.0 μM and a detection limit of 330 nM. The reproducibility was 2.2 % using one MWCNTs-POMAF dispersion, and 3.9 % using 4 different dispersions. The sensor was successfully used for the quantification of hydrogen peroxide in enriched milk samples. © 2021 Wiley-VCH GmbH